An apparatus to convert cylindrical shaped objects to flat sheet objects and a method thereof - Bakar, Edi Suhaimi; Ashaari, Zaidon; Jusoh, Mohd Zin; Mohd Sharani, Dzafarin (2012)

(untitled)
The present invention relates to an apparatus to convert cylindrical shaped hollow object to flat sheet objects. The apparatus is securely positioned onto a worktable and wherein the said worktable comprises of a four leg structure supporting a base. The said apparatus comprises of a cutterhead, a workpiece feeding mechanism and a workpiece holding mechanism and wherein the cutterhead, workpiece feeding mechanism and workpiece holding mechanism are secured onto the said worktable and wherein the cutter head is comprises of radial cutter and wherein the said cutterhead includes three different angled radial cutters of 15°, 20° and 25° to produce grooving angle.